2004
DOI: 10.57054/jhea.v2i2.1676
|View full text |Cite
|
Sign up to set email alerts
|

4 - Student Loans in Kenya: Past Experiences, Current Hurdles, and Opportunities for the Future

Abstract: Kenya has a long history of lending to students; but in the 1980s, the program was criticized for its poor administration, high costs, and low recovery rates. The estab- lishment of the Higher Education Loans Board in 1995 ushered in reforms that have broadened the program beyond the public universities to other postsecondary institutions and to some students in Kenya’s growing private sector and improved loan recoveries. This article describes these efforts to improve recoveries and makes a number of recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Much of it consists of policy analysis, studies of access to higher education and the changing nature of supply and demand more generally from a policy perspective. Some examples include literature on higher education finance (Gudo 2014;Johnstone 2006;Otieno 2004) and rate-of-return analysis (Kimenyi, Mwabu and Manda 2006). Rate-of-return analyses focus on the extent to which an education system yields returns to individuals and the economy that justify the resources invested in the education system.…”
Section: Rate Of Return and The Public Good In Kenyamentioning
confidence: 99%
“…Much of it consists of policy analysis, studies of access to higher education and the changing nature of supply and demand more generally from a policy perspective. Some examples include literature on higher education finance (Gudo 2014;Johnstone 2006;Otieno 2004) and rate-of-return analysis (Kimenyi, Mwabu and Manda 2006). Rate-of-return analyses focus on the extent to which an education system yields returns to individuals and the economy that justify the resources invested in the education system.…”
Section: Rate Of Return and The Public Good In Kenyamentioning
confidence: 99%
“…To motivate this assumption, it is observed that bankers in small countries have expressed reluctance to make student loans given the uncertainty of debt repayment in light of the established patterns of skilled emigration (Khraiche, 2011). 8 Similarly, Kenya, which does provide students loans to cover public and private education, has historically faced difficulty in collecting repayment partly because of emigration and poor record keeping and enforcement (Otieno, 2004). The phenomenon of debtors leaving a country and avoiding debt repayment was also a serious concern in Dubai in 2009, as indebted expatriates made unemployed by the financial crisis began leaving the country, debts unpaid (Worth, 2009).…”
Section: Household Type Ii: Those Who Desire To Migratementioning
confidence: 99%